1984
DOI: 10.1266/jjg.59.133
|View full text |Cite
|
Sign up to set email alerts
|

The amount of polymorphism and genetic differentiation in natural populations of the haploid liverwort Conocephalum conicum.

Abstract: Natural populations of diploid organisms are expected to be more polymorphic than haploid organisms under most selection models. To test this prediction and to obtain data concerning the amount of allozyme polymorphism in a haploid plant, I examined two natural populations of the haploid liverwort Conocephalum conicum by starch gel electrophoresis.Abundant genie variability was found within local populations in Japan: 7 of 11 loci. Average heterozygosity of these 11 loci was 0.167. This value is similar to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…However, several studies on haploid microorganisms (Milkman 1973, Spieth 1975 show no obvious differences from diploids. Recently, Yamazaki (1984) reported that the amount of heterozygosity in the haploid liverwort Concocephalum (H=0.167) was similar to that obtained for various kinds of diploid organisms.…”
Section: Introductionsupporting
confidence: 62%
“…However, several studies on haploid microorganisms (Milkman 1973, Spieth 1975 show no obvious differences from diploids. Recently, Yamazaki (1984) reported that the amount of heterozygosity in the haploid liverwort Concocephalum (H=0.167) was similar to that obtained for various kinds of diploid organisms.…”
Section: Introductionsupporting
confidence: 62%
“…A better understanding of mechanisms responsible for the evolutionary pattern in liverwort H3 genes can be provided by the studies of H3 genes in other closely related taxa and other multigene families in the same species. However, this study confirmed clearly that liverwort maintain much genetic variation at the DNA level, and supports the previous results of Yamazaki (1984Yamazaki ( , 1986 and Kim at al. (1996).…”
Section: Discussionsupporting
confidence: 92%
“…This hypothesis on the opinion about slow evolution had been supported by wide geographical ranges of respective species, the high similarity between fossil and extant species, and the low number of known species in spite of being an old plant group. However, studies on genetic variability in liverwort indicated that some species are internally differentiated in their morphological (Lewis and Smith, 1977;Longton, 1974;Schuster, 1981;Akiyama and Hiraoka, 1994), physiological (Briggs, 1972;Hatcher, 1967), cytological (Newton, 1977(Newton, , 1981 and chemical aspects (Markham, 1976;Toyata, 1994;Szweykowski et al, 1981;Zehr, 1980;Odrzykoski and Szweykowski, 1991;Akiyama and Hiraoka, 1994;Yamazaki, 1981Yamazaki, , 1984Kim at al., 1996; for review, Stoneburner et al, 1991). Some authors suggested that the levels of variability and microevolutionary processes in liverworts resemble those noted in higher plants (Smith, 1979;Krzakowa and Szweykowski, 1979) and animals (Yamazaki, 1981(Yamazaki, , 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Geographically distant populations of the thalloid liverwort Conocephalum conicum (Hepaticae, Marchantiales) have been recently intensively studied for variation of flavonoids (Markham et al, 1976), terpenoids (Suire and Asakawa, 1981), volatile components (Toyota, 1994;Toyota et al, 1997) and isozymes (Szweykowski and Krzakowa, 1978;Szweykowski, Odrzykoski and Zielinski, 1981;Yamazaki, 1981Yamazaki, , 1984Odrzykoski and Szweykowski, 1991;Akiyama and Hiraoka, 1994;Kim et al, 1996). Population studies have revealed significant local and regional differentiation.…”
Section: Introductionmentioning
confidence: 99%